Higher-Order Thinking Skills in Science Teacher Education: A Bibliometric Analysis Over the Last 11 Years - Rifatul Himmah; Elsa Monica; Moch Faizul Huda; Steven Taniwan; Salma Hasna Hamiydah; Muhammad Rey Dafa Ahmadi (Journal of Law and Bibliometrics Studies, 2027)
Objective: This study examines the research landscape of higher-order thinking skills (HOTS) in science teacher education within the framework of Education for Sustainable Development (ESD) from 2015 to 2025, addressing the limited integration of HOTS, science teacher education, and ESD in previous bibliometric studies. Methods: A bibliometric analysis was conducted using Scopus-indexed journal articles. After screening using PRISMA 2020, 108 articles were analyzed using Bibliometrix/Biblioshiny to examine publication trends, influential contributors, and thematic development. Results: HOTS research has grown substantially over the past decade, with the highest number of publications recorded in 2025. Indonesia emerged as a leading contributor, while the International Journal of Science Education (7 publications) and Sustainability (6 publications) were the most prolific journals. Thematic analysis identified four major thematic clusters, revealing a conceptual shift from individual cognitive skills toward inquiry-based learning, project-based learning, teacher education, sustainability, and generative artificial intelligence. Novelty: This study extends existing bibliometric research by integrating higher-order thinking skills, science teacher education, and Education for Sustainable Development within a single analytical framework, providing a more comprehensive understanding of the field's intellectual structure, thematic evolution, and future research directions.